Hip Angle Behavior in Landing After Drop Jump in Children; and their Implicance in Prevention Programs - Jair Burboa G; Matias Bahamondes F; Mauricio Inostroza M; Paloma Lillo U; Jaime Hinzpeter (Journal of Sports and Exercise Medicine, 2019)
Background The Anterior Cruciate Ligament (ACL) injury is uncommon, but constitutes an important percentage of the lesions requiring more than 8 weeks of recovery in sports. Most ACL injuries do not require external contact and are associated with biomechanical risk factors that stress this ligament ACL: like an increase in knee valgus angle (KV) and hip flexion (HF) and a decreased in knee flexion (KF). The ACL requires muscle cooperation to resist the load; however, when there is fatigue, the protective capacity of the musculature would decrease. The objective of the study is to analyze the angular behavior before and after a physical load for HF in children of 14-15 years old. Hypothesis The physical load applied in a single training session is enough to change some biomechanical risk factors of ACL injury. Study Design Experimental study Level of Evidence 2b Methods The sample consisted of 50 students from different soccer schools between 14-15 years old. We analyzed the hip angular behavior of hip flexion before and after a training session. The angles where obtained from inertioal sensor while the students performed a Drop Jump test from a 30 centimeters drawer. Results Statistically significant differences were found in the differences between pre physical load HF / post-load HF (p = 0.00053), right pre physical load HF / right post- load HF (p = 0.0086) and left post- load (p = 0.0248206). Conclusions It was concluded that the angular behavior of HF increases significantly in both post-training limbs, after performing a physical load. Clinical Relevance This study analyzed the importance of using prevention injury programs since early stages, and give importance to the eccentric role of hamstring, gluteus and core exercises.
Keywords: Anterior Cruciate Ligament (ACL)